First confirmed case of spondylodiscitis with epidural abscess caused by Parvimonas micra. Issue 11 (November 2015) - Endo, Shiro; Nemoto, Tadanobu; Yano, Hisakazu; Kakuta, Risako; Kanamori, Hajime; Inomata, Shinya; Ishibashi, Noriomi; Aoyagi, Tetsuji; Hatta, Masumitsu; Gu, Yoshiaki; Kitagawa, Miho; Kaku, Mitsuo
Abstract Parvimonas micra was renamed species as within Gram-positive anaerobic cocci and rarely causes severe infections in healthy people. We report the first confirmed case of spondylodiscitis with epidural abscess caused by P. micra in a healthy women. The patient has a pain in low back and anterior left thigh. Magnetic resonance imaging and computed tomography detected the affected lesion at the L2 and L3 vertebral bodies. All isolates from the surgical and needle biopsy specimens were identified as P. micra by 16S rRNA and MALDI-TOF. In this case, P. micra showed high sensitivity to antimicrobial therapy. She was successfully treated with debridement and sulbactam/ampicillin, followed by oral metronidazole for a total of 10 weeks. The causative microorganisms of spondylodiscitis are not often identified, especially anaerobic bacteria tend to be underestimated. On the other hand, antimicrobial therapy for spondylodiscitis is usually prolonged. Accordingly, we emphasize the importance of performing accurate identification including anaerobic bacteria.